Perbandingan dosis pupuk NPK mutiara dan pupuk kandang ayam terhadap pertumbuhan dan hasil tanaman tomat (Licopersicun eskulantum Mill) - Yulianto, Doni Hermawan Dwi; Hartanto, Kristianus Heri (AGRICOLA, 2023)
This study was conducted with the aim to obtain a combination of NPK M and soil doses of manure that is appropriate to the growth and yield of tomato soil. Then to find out the right dose of NPK M on the growth and yield of tomato soil. And the next result is to find out the combination of soil: the right manure to the growth and yield of tomato soil. This research was conducted on February 1, 2023 to June 1, 2023 at Pak Utan Village, Toho District, Mempawah Regency, Batar Kalimantan. this research method is a factorial design used in a Completely Randomized Design consisting of two factors and further analysis compared with the analysis of variance (analysis of variance) at 5% each. To determine the difference between the measurements carried out DMRT Test (Duncan multiple Range Test) at a real rate of 5 %. 7 grams of NPK M gives the best results on parameters in tomato plants, namely fresh root weight, dry root weight, and number of fruits. This is because the measured nutritional needs of plants so that the growth process of vegetative and generative plants can be seen clearly and can provide an increase in yields that are quite optimal. The parameters given can be utilized by farmers, namely the dosage of each fertilizer applied in accordance with the development of soil development.